Attentional demands influence vocal compensations to pitch errors heard in auditory feedback. - Anupreet K Tumber; Nichole E Scheerer; Jeffery A Jones (PLoS ONE, 2014)
Auditory feedback is required to maintain fluent speech. At present, it is unclear how attention modulates auditory feedback processing during ongoing speech. In this event-related potential (ERP) study, participants vocalized/a/, while they heard their vocal pitch suddenly shifted downward a ½ semitone in both single and dual-task conditions. During the single-task condition participants passively viewed a visual stream for cues to start and stop vocalizing. In the dual-task condition, participants vocalized while they identified target stimuli in a visual stream of letters. The presentation rate of the visual stimuli was manipulated in the dual-task condition in order to produce a low, intermediate, and high attentional load. Visual target identification accuracy was lowest in the high attentional load condition, indicating that attentional load was successfully manipulated. Results further showed that participants who were exposed to the single-task condition, prior to the dual-task condition, produced larger vocal compensations during the single-task condition. Thus, when participants' attention was divided, less attention was available for the monitoring of their auditory feedback, resulting in smaller compensatory vocal responses. However, P1-N1-P2 ERP responses were not affected by divided attention, suggesting that the effect of attentional load was not on the auditory processing of pitch altered feedback, but instead it interfered with the integration of auditory and motor information, or motor control itself.